Valuation and Action Recommendations on the Control Panel of PT Bukaka Teknik Utama Duri's Pumping Unit Using Failure Mode and Effect Analysis (FMEA) : Valuasi dan Rekomendasi Tindakan Pada Panel Kontrol Pumping Unit PT Bukaka Teknik Utama Site Duri Menggunakan Failure Mode and Effect Analysis(FMEA) - Putut Son; Alif Miratul Ansyari; Elva Susianti (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2025)
PT Bukaka Teknik Utama Site Duri is a company engaged in the oil and gas equipment sector and collaborates with PT Chevron Pacific Indonesia in managing sucker rod pump type pumping units for crude oil extraction processes. The pumping units are powered by 75 HP electric motors that are controlled and monitored through a control panel. The control panel plays an important role in maintaining operational reliability and safety as it is equipped with various protection components, such as overload, over voltage, over current, and thermal protection. However, based on operational data, there are still control panel malfunctions that cause pump operations to stop and daily oil production targets to not be achieved, as well as increasing the risk of damage to the drive motor. This study aims to conduct a risk assessment and provide recommendations for improvements to the pumping unit control panel using the Failure Mode and Effect Analysis (FMEA) method. The FMEA analysis results show that the contactor and overvoltage components have the highest risk levels, while the fuse and MCB have the lowest risk levels. The recommended actions include replacing components with higher specifications and implementing preventive measures such as repairing the grounding system and adding protection against moisture and dust. The implementation of these recommendations is expected to reduce the failure rate and improve the reliability of the control panel in the next operational period.